2019
DOI: 10.1002/admt.201900528
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Transient Radio Frequency Antennas: Toward Triggered Wireless Transient Circuits

Abstract: While implantable medical devices offer tremendous potential for treating a myriad of diseases and disorders, there are many situations in which such devices are only needed for short time periods, with extended presence or surgical removal leading to a host of undesired complications. To address this concern, researchers are working to develop implantable circuitry that eventually disintegrates. Prior work in this area leveraged known bioresorbable materials, but the lifetime of circuits formed from such mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…The results showed that the cellulose concentration increase contributed to the decrease in the LCST of the copolymer. The LCST decrease was likely due to the increase in the ratio of hydrophobic cellulose monomers to hydrophilic methylcellulose monomers [23,24]. With a higher fraction of the hydrophobic cellulose moieties conjugated, the cellulose-methylcellulose copolymer is more prone to aggregation into core-shell micelles.…”
Section: Effect Of Nanocrystal Concentrations On the Lcstmentioning
confidence: 99%
“…The results showed that the cellulose concentration increase contributed to the decrease in the LCST of the copolymer. The LCST decrease was likely due to the increase in the ratio of hydrophobic cellulose monomers to hydrophilic methylcellulose monomers [23,24]. With a higher fraction of the hydrophobic cellulose moieties conjugated, the cellulose-methylcellulose copolymer is more prone to aggregation into core-shell micelles.…”
Section: Effect Of Nanocrystal Concentrations On the Lcstmentioning
confidence: 99%
“…Stimuli-responsive materials have many potential applications due to their ability to respond dramatically to small environmental changes. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Temperature-responsive materials are particularly attractive as temperature is easy to control and is orthogonal to other relevant environmental conditions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] One possible application of such materials is to enable thermal initiation of mixing of separate payloads.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Temperature-responsive materials are particularly attractive as temperature is easy to control and is orthogonal to other relevant environmental conditions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] One possible application of such materials is to enable thermal initiation of mixing of separate payloads. This can be achieved through dramatic temperature-dependent transformation of a constraining material, allowing release from encapsulation, 2,[6][7][8]13,14 ow through a blockade or valve, [9][10][11][12] or the owing together of previously distinct solid-like gels.…”
Section: Introductionmentioning
confidence: 99%
“…Transient electronics that can dissolve or disappear under external or internal stimulus has aroused great interest in biology, [1][2] healthcare, [3][4] data storage, [5][6] and consumer electronics. [7][8][9] Transient electronic devices are typically constructed by nano/microscale thin films made of materials such as Mg, Zn, Si, SiO 2 , MgO, and ZnO that are degradable or dissolv-substrates to poly(vinyl alcohol) (PVA) substrates. The resulting transient films were 10 × 10 cm 2 in dimension with controllable thickness ranging from 60 to 440 nm and conductivities from 5.26 × 10 −2 to 1.92 × 10 4 S m −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Transient electronics that can dissolve or disappear under external or internal stimulus has aroused great interest in biology, [ 1–2 ] healthcare, [ 3–4 ] data storage, [ 5–6 ] and consumer electronics. [ 7–9 ] Transient electronic devices are typically constructed by nano/microscale thin films made of materials such as Mg, Zn, Si, SiO 2 , MgO, and ZnO that are degradable or dissolvable when interacting with environmental molecules such as water, enzymes, and oxygen. [ 10–11 ] Despite that many innovative works in transient electronics have yielded diverse devices such as sensors, [ 12–14 ] power suppliers, [ 15–17 ] passive components, [ 18 ] and transistors, [ 19–21 ] the category of transient electronics remains inadequate as compared with other types of electronic devices, making construction of fully transient integration circuits extremely challenging due to limited selection in transient chips and devices.…”
Section: Introductionmentioning
confidence: 99%